Association Between Breastfeeding, Parents’ Body Mass Index and Birth Weight with Obesity Indicators in Children - De Moraes-Ferrari, G (BioMed Central Ltd, 2022)
Background: Childhood obesity is potentially affected by breastfeeding, parents’ body mass index and birth weight. Thus, this study aimed to verify the association between breastfeeding, parents’ body mass index and birth weight with obesity indicators in children. Methods: This is a cross-sectional study, including data from 402 schoolchildren between 9 and 11 of age in the city of São Caetano do Sul, Brazil. Parents or guardians answered a questionnaire about breastfeeding (month), birth weight (kg), and parental body weight and height (parents’ body mass index [kg/m2] was calculated). Body mass index (kg/m2), waist circumference (cm) and body fat (%), determined via bio-impedance, were measured and used as obesity indicators. Multi-level linear regression models were used to assess the respective associations adjusted for the potential confounders. Results: Considering body mass index of children, the overall prevalence of eutrophic, overweight and obese were 58.2%, 20.9% and 17.2%, respectively. Significant and positive correlations were observed between breastfeeding, maternal as well as paternal body mass index and the children’s body mass index, body fat and waist circumference. Birth weight was weakly and positively associated with body mass index and body fat but was not associated with waist circumference. After adjusting for school, sex, age, race/ethnicity, annual household income, sedentary time and moderate-to-vigorous physical activity, maternal body mass index and birth weight were positively associated with children’s body mass index (β: 0.228; 95%CI: 0.142; 0.314 and β: 0.001; 95%CI: 0.001; 0.002), body fat (β: 0.484; 95%CI: 0.297; 0.671 and β: 0.002; 95%CI: 0.001; 0.003) and waist circumference (β: 0.509; 95%CI: 0.304; 0.715 and β: 0.003; 95%CI: 0.001; 0.005). Breastfeeding was not associated with any obesity indicators. Conclusion: Maternal body mass index and birth weight were associated with children’s obesity indicators. The perinatal environment, therefore, appears to be a critical contributor to childhood obesity and public policies need to address parental obesity in order to tackle childhood obesity. Trial registration:: The International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE) is registered at (Identifier NCT01722500). © 2022, The Author(s).